2013
DOI: 10.1111/opn.12041
|View full text |Cite
|
Sign up to set email alerts
|

Skin cleansing practices for older people: a systematic review

Abstract: Skin cleansing is one of the cornerstones of nursing practice, however, in the absence of a robust evidence base most such care is currently based on 'custom and practice'. There is a need to conduct further research into cleansing practices that will maintain or enhance skin health and skin integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…Bathing has been argued to have an effect on patient well-being [4] and patient comfort [5]. Furthermore, preserving skin integrity and personal hygiene are proposed to be important physiological functions of bathing, which in turn prevent infections and disease [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Bathing has been argued to have an effect on patient well-being [4] and patient comfort [5]. Furthermore, preserving skin integrity and personal hygiene are proposed to be important physiological functions of bathing, which in turn prevent infections and disease [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Four 3-5 , 22 of 7 systematic reviews showed good methodological quality; they met 6 or more out of 11 quality criteria according AMSTAR. The most common reasons for the poor ratings were: (1) no protocol was published a priori, 2,4,5,13,21 (2) excluded studies were not listed, 2,4,5,13,21,22 or (3) a confl ict of interest was not specifi ed for the systematic review and for each of the included studies 2-5 , 13 , 21 , 22 ( Table 1 ).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…), clinical quality and risk management (A.H.). Based on feedback from these expert colleagues, the algorithm was 13 Kottner et al (2013) 5 Moore and Webster …”
Section: Development Of the Skin Care Algorithmmentioning
confidence: 99%
“…[1][2][3][4][5][6] Still, there are very few studies and research to validate, whether the new bath technology is better than the wellknown basin-type with soap and water. Only a few studies describe [1,2,[5][6][7][8][9][10] the patients' and the nurses' attitude, experiences and evaluations of using the two methods. In home care-settings no studies are found, where the two types of nurse-assisted baths are explored, why it necessary to conduct this study in a home-care setting.…”
Section: Introductionmentioning
confidence: 99%
“…[9] A randomized clinical study from 2014 concluded, that most patients diagnosed with heart failures in an intensive care unit preferred the disposable bath. [1] Present literature research illustrate [1,2,[5][6][7][8][9][10] that the costbenefit effect is a dominating and underlying aim for the four other areas found, i.e. the microbiology, the skin quality, the satisfaction, and the traditional versus the new method of nurse assisted personal hygiene to older adults in homecare settings.…”
Section: Introductionmentioning
confidence: 99%